Antioxidant and Antidiabetic Potential of Extracts from Selected Species of Smilax L. - Adhikari, Sirjana; Pant, Deepak Raj; Joshi, Giri Prasad (Journal of Nepal Biotechnology Association, 2025)
Smilax is a potential medicinal plant of the family Smilacaceae, distributed in Nepal's tropical, sub-tropical, and temperate zones. The present work focuses on preliminary phytochemical analysis, antioxidant properties, and antidiabetic activity of methanolic extracts from four different species of Smilax. Preliminary qualitative analysis had shown the presence of almost all tested secondary metabolites in methanolic extracts. Although, antioxidant activity was shown by all species of Smilax, the lowest IC50 value was found in methanolic extract of S. ferox. Percentage α-amylase inhibition activity was highest in the methanolic extract of S. perfoliata (79.13%) and lowest in S. lanceifolia (50.0%). Similarly, the highest percentage of α-Glucosidase inhibition activity was shown by the methanolic extract of S. lanceifolia (98.08%) and the lowest by S. perfoliata (29.71%). The present findings pave the way for a further comprehensive phytochemical investigation to validate their medicinal properties.